Person-to-Person Transmission of Andes Virus in Hantavirus Pulmonary Syndrome, Argentina, 2014 - Daniel O. Alonso; Unai Pérez-Sautu; Carla M. Bellomo; Karla Prieto; Ayelén Iglesias; Rocío Coelho; Natalia Periolo; Isabel Domenech; Gabriel Talmon; Romina Hansen; Gustavo Palacios; Valeria P. Martinez (Emerging Infectious Diseases, 2020)
Andes virus is unique among hantaviruses because it can be transmitted from person to person. This mechanism was previously supported by epidemiologic data and genetic evidence based only on partial sequences. We used full-length virus sequencing to confirm person-to-person transmission of this virus in a cluster of 3 cases in Argentina in 2014.